Size Distribution of Boulders in the Subsurface Layer of Asteroid Dimorphos Revealed by the Ejecta Pattern Observed in the DART Exploration - Toshihiko Kadono; Takafumi Ootsubo (Advances in Astronomy)
We analyze the pattern observed in the ejecta curtain induced by hypervelocity impact to investigate the dependence of the pattern on the size distributions of target particles. When target particles have a similar size, the characteristic size of the patterns is smaller than the size of the entire curtain. On the contrary, when particles in a wide size range are mixed, the pattern exhibits a large-scale structure and the characteristic size of the pattern becomes larger or comparable to the ejecta curtain scale. Based on the relationship between the pattern in the ejecta curtain and the size distribution of target particles, the pattern observed in the DART exploration suggests that the subsurface layer of Dimorphos consists of particles of a wide size range being mixed. This should be revealed by the follow-up Hera exploration.